Prairie dog song : the key to saving North America's grasslands - Roth, Susan L.; Trumbore, Cindy (Lee & Low Books Inc., 2016)
"Cumulative text based on an old folksong alternating with additional scientific information explores the role of prairie dogs, a keystone species in North America's grasslands, and conservation efforts to restore the balance of plants and animals of the Janos, Mexico, prairie dog complex. Backmatter includes timeline, photographs, music, prairie dog facts, glossary, and authors' sources"--